2021
DOI: 10.1177/1747493021991972
|View full text |Cite
|
Sign up to set email alerts
|

Absent hyperdense middle cerebral artery sign is associated with poor functional outcome after mechanical thrombectomy

Abstract: Background The hyperdense middle cerebral artery sign on computed tomography indicates proximal middle cerebral artery occlusion. Recent reports suggest an association between the hyperdense sign and successful reperfusion. The prognostic value of the hyperdense middle cerebral artery sign in patients receiving mechanical thrombectomy has not been extensively studied. Aims Our study aims to evaluate the association between the hyperdense middle cerebral artery sign and functional outcome in patients with M1 oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
5
13
1
Order By: Relevance
“…On the contrary, Ume et al demonstrated that absent HMCAS predicts worse functional outcomes in patients with M1 occlusions treated with mechanical thrombectomy [23]. The authors attributed the difference to exclusion of patients with distal M2 occlusion, who inherently carry a more favorable outcome [23]. However, this does not explain our ndings: the good outcome at 90-day was comparable among the negative HMCAS, proximal HMCAS, and distal HMCAS groups.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…On the contrary, Ume et al demonstrated that absent HMCAS predicts worse functional outcomes in patients with M1 occlusions treated with mechanical thrombectomy [23]. The authors attributed the difference to exclusion of patients with distal M2 occlusion, who inherently carry a more favorable outcome [23]. However, this does not explain our ndings: the good outcome at 90-day was comparable among the negative HMCAS, proximal HMCAS, and distal HMCAS groups.…”
Section: Discussioncontrasting
confidence: 64%
“…Another study conducted by Mowla et al showed a similar result in patients receiving bridging therapy [17]. On the contrary, Ume et al demonstrated that absent HMCAS predicts worse functional outcomes in patients with M1 occlusions treated with mechanical thrombectomy [23]. The authors attributed the difference to exclusion of patients with distal M2 occlusion, who inherently carry a more favorable outcome [23].…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Ume et al reported that the hyperdense middle artery sign was associated with favorable outcomes and lower mortality using modern mechanical devices ( 26 ). In our study, favorable outcomes and mortality were not significantly different for patients with or without HBAS after EVT.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicate that the sensitivity of the hyperdense MCA sign on MIP images was significantly higher than that on averaged images. Hyperdense sign was first reported as “hyperdense MCA sign,” and the usefulness of the hyperdense sign have been reported especially in MCA [ 1 , 6 ]. Furthermore, in terms of the frequency of acute occlusions, MCA occlusions are more common than anterior cerebral artery, posterior cerebral artery, and vertebral and basilar arterial occlusions [22], and endovascular thrombectomy is strongly recommended for acute cerebral large vessel occlusion of the internal carotid artery or M1 segment of the middle cerebral artery [23].…”
Section: Discussionmentioning
confidence: 99%
“…Given that mechanical thrombectomy (MT) has become a standard therapy in acute stroke patients with the internal carotid artery or MCA occlusion, there is a growing demand for rapid access to the imaging examination that can confirm the presence of thromboembolic event. Several studies addressed the relationship between the presence of hyperdense MCA sign and prognosis after MT [ 4 6 ]. However, the use of the hyperdense MCA sign is limited because of the low sensitivity for the detection of thromboembolism [ 7 ].…”
Section: Introductionmentioning
confidence: 99%